Eukaryotic yeast V1-ATPase rotary mechanism insights revealed by high-resolution single-molecule studies - Yanagisawa, Seiga; Bukhari, Zain A.; Parra, Karlett J.; Frasch, Wayne D. (Frontiers in Molecular Biosciences, 2024)
Vacuolar ATP-dependent proton pumps (V-ATPases) belong to a super-family of rotary ATPases and ATP synthases. The V 1 complex consumes ATP to drive rotation of a central rotor that pumps protons across membranes via the Vo complex. Eukaryotic V-ATPases are regulated by reversible disassembly of subunit-C, V 1 without C, and VO. ATP hydrolysis is thought to generate an unknown rotary state that initiates regulated disassembly. Dissociated V 1 is inhibited by subunit-H that traps it in a specific rotational position. Here, we report the first singlemolecule studies with high resolution of time and rotational position of S. cerevisiae V 1 -ATPase lacking subunits H and C (V 1 DHC), which resolves previously elusive dwells and angular velocity changes. Rotation occurred in 120° power strokes separated by dwells comparable to catalytic dwells observed in other rotary ATPases. However, unique V 1 DHC rotational features included: (1) faltering power stroke rotation during the first 60°; (2) a dwell often occurring ~45° after the catalytic dwell, which did not increase in duration at limiting MgATP; (3) a second dwell, ~2-fold longer occurring ~112° that increased in duration and occurrence at limiting MgATP; (4) limiting MgATP-dependent decreases in power stroke angular velocity where dwells were not observed. The results presented here are consistent with MgATP binding to the empty catalytic site at ~112° and MgADP released at 45°, and provide important new insight concerning the molecular basis for the differences in rotary positions of substrate binding and product release between V-type and F-type ATPases.